“The Nuruls”: A Sociolinguistic Study of Name Enregisterment in Indonesian Online Discourse - Fakhira, Rifda; Amaly, Najla (Alhadharah: Jurnal Ilmu Dakwah, 2024)
The emerging trend of using first name as a register to address a specific kind of social and linguistic behaviour has been getting more common. This phenomenon is related to a linguistics process that is known as enregisterment (Agha, 2003). The current study examines the enregisterment process of the name "Nurul" into a characterological figure and how it intersects with the language and social ideologies among the Indonesian youth on the social media platform X. The study employed a qualitative content analysis, with the data taken from posts that contain the word "Nurul" from the platform X. Furthermore, the data was analysed with critical discourse analysis (CDA) and feminist critical discourse analysis (FCDA). The result of the study finds that “Nurul” is said to be a religious girl but has a hypocritical nature to the name which does not reflect the Islamic values. "Nurul" functions as a critique of sexism and patriarchal conventions. However, it also underlined the possibility of gender stereotypes and marginalising women.